2019
DOI: 10.9734/afsj/2019/v13i130097
|View full text |Cite
|
Sign up to set email alerts
|

Control of Aflatoxin Production in Cassava Produced by Dry Fermentation in North Kivu, Democratic Republic of Congo

Abstract: Traditionally, cassava (Manihot esculenta Crantz) is transformed by fermentation in water (retting) or in the open air (dry fermentation) in the DRC. In the east of the country (North Kivu), dry fermentation is the main technique for processing cassava for its detoxification and conservation. The Congolese farmers ferment the cassava to the open air using a preselected microferment contained in the scrapings of the fermented cassava previously called "MUSIYIRO". These fermentations are spontaneously directed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…During drying, Akuoga products are usually spread on soil for longer periods to completely dry compared to Abeta. Similar studies have reported that the process of fermentation favours the growth of several organisms including Aspergillus fumigatus, A. niger, and A. flavus, in particular, high humidity, temperature, and favourable pH of 5-6 conditions [19][20][21]. A survey by Kaaya and Eboku [22] demonstrated that in Kumi district, Eastern Uganda, fermented cassava chips are more contaminated with moulds and yeasts than nonfermented.…”
Section: Yeast and Mould Contaminationmentioning
confidence: 80%
“…During drying, Akuoga products are usually spread on soil for longer periods to completely dry compared to Abeta. Similar studies have reported that the process of fermentation favours the growth of several organisms including Aspergillus fumigatus, A. niger, and A. flavus, in particular, high humidity, temperature, and favourable pH of 5-6 conditions [19][20][21]. A survey by Kaaya and Eboku [22] demonstrated that in Kumi district, Eastern Uganda, fermented cassava chips are more contaminated with moulds and yeasts than nonfermented.…”
Section: Yeast and Mould Contaminationmentioning
confidence: 80%
“…Specifically, it assesses the extent of women's participation in various stages of groundnut management. Third, the "who" dimension primarily focuses on women groundnut farmers while also involving other actors such as local leaders, extension officers, and project representatives [25][26][27]. The study posits that participation is a comprehensive framework encompassing diverse elements essential for understanding and addressing rural development challenges.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Women, who are predominantly involved in the groundnut postharvest value chain, play a crucial role in addressing this challenge [5][6][7]. In many developing countries, groundnuts are often referred to as the "women's crop" [8][9][10][11][12]. This is because groundnuts provide rural women with subsistence, nutrition, and food security through their active participation in the postharvest value chain [8,13].…”
Section: Introductionmentioning
confidence: 99%